EFFECTIVENESS OF SCHEMATIC REPRESENTATION IN SOLVING WORD PROBLEM - Rahmad Bustanul Anwar; Dwi Rahmawati; Sri Endang Supriyatun (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Schematic representation is very important for students to solve problems in solving word problems. There are two types of schematic representation namely pure schematic representation and mixed schematic representation. The process of forming a pure schematic representation tends to be more concise than the process of forming a mixed schematic representation. So it is necessary to investigate in more detail and in-depth which is more effective between pure schematic representation or mixed schematic representation in helping students to solve word problems. This study aims to determine the effectiveness of pure schematic representation and mixed schematic representation in solving word problems. The effectiveness mentioned in this study is the accuracy and precision of the schematic representation formed by the students when solving word problems. This study uses a qualitative approach involving students from grade IX in Metro City, Lampung, Inonesia as research subjects. The students involved in this study were 60 students. Of the 60 students, two were selected as research subjects representing pure schematic representation and mixed schematic representation. Both subjects were chosen considering the possibility of forming a schematic representation and having good communication skills. The results of this study indicate that students who form pure schematic representation present information and schematic drawings formed in a more concise, precise and accurate manner. While students who form a mixed schematic representation by presenting less structured information, the schematic drawings formed are longer. So it can be concluded that a pure schematic representation is more effective than a mixed schematic representation for solving word problems.Keywords: Representations; mixed schematic representations; pure schematic representations; word problem. AbstrakRepresentasi skematis sangat penting bagi siswa untuk mengurai masalah dalam menyelesaikan word problem. Terdapat dua jenis representasi skematis yaitu representasi skematis murni dan representasi skematis campuran. Proses terbentuknya representasi skematis murni cenderung lebih ringkas (pendek) dibandingkan dengan proses terbentuknya representasi skematis campuran. Maka perlu diselidiki lebih detail dan mendalam manakah yang lebih efektif antara representasi skematis murni atau representasi skematis campuran dalam membantu siswa selama menyelesaikan word problem. Penelitian ini bertujuan untuk mengetahui efektivitas antara representasi skematis murni dan representasi skematis campuran dalam pemecahan word problem. Efektivitas yang dimaksud dalam penelitian ini adalah ketepatan dan keakuratan representasi skematis yang dibentuk siswa selama menyelesaikan word problem. Penelitian ini menggunakan pendekatan kualitiatif yang melibatkan siswa kelas IX di Kota Metro, Lampung, Indonesia sebagai subjek penelitian. Siswa yang terlibat dalam penelitian ini berjumlah 60 siswa. Dari 60 siswa dipilih dua siswa sebagai subjek penelitian yang mewakili representasi skematis murni dan representasi skematis campuran. Dua subjek tersebut dipilih melalui pertimbangan mampu membentuk representasi skematis dengan baik, dan memiliki kemampuan komunikasi yang baik. Sebuah tes diberikan untuk mengetahui kemampuan siswa dalam membentuk representasi skematis. Hasil pekerjaan siswa yang terkumpul dianalisis dan digunakan sebagai bahan dalam wawancara untuk menggali informasi bagaimana siswa membentuk representasi skematis. Hasil penelitian ini menunjukkan bahwa siswa yang membentuk representasi skematis murni menyajikan informasi-informasi dan gambar skema yang dibentuk lebih ringkas, tepat dan akurat. Sedangkan siswa yang membentuk reprsentasi skematis campuran dalam menyajikan informasi-informasi kurang terstruktur, dan gambar skema yang dibentuk lebih panjang. Sehingga dapat disimpulkan bahwa representasi skematis murni lebih efektif daripada representasi skematis campuran selama menyelesaikan word problem.Kata kunci: Representasi; representasi skematis campuran; representasi skematis murni; word problem.